ELECTRONIC-WORD OF MOUTH AND PRODUCT QUALITY ON BUYING INTEREST THROUGH TRUST IN ONLINE SHOPS - Harjadi, Dikdik; Suhardi, Dadang; Ayisiyah, Nur (TRIKONOMIKA, 2019)
This research aims at investigating the influence of e-WOM and product quality on buying interest through the customers’ trust. This research used a quantitative research design with survey method. This research employed descriptive and verification research methods. A path analysis was conducted to analyze the interval data in this research. The result of data analysis and hypothesis testing revealed that e-WOM and product quality had an influence on customers’ trust in online shops, e-WOM had an influence on the customers’ trust in online shops, product quality had an influence on customers’ trust in online shops, while e-WOM, product quality, and the customers’ trust had an influence on buying interests in online shops, e-WOM had an influence on buying interests in online shops, product quality had an influence on buying interests in online shops, and the customers’ trust had an influence on buying interests in online shops.